ILLEGAL EVIDENCE IN CASE LAW - Pisarić, Milana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
Certain evidence in certain cases can not be used to establish the facts in criminal proceedings, in the sense that the court judgment is based upon them, because such evidence are by the nature or the way of acquiring them contrary to certain rules. Since the Criminal Procedure Code regarding the illegal evidence remained somewhat vague, and that the use of such evidence is determined as a relatively essential violation of the criminal procedure, the court has a crucial role to play with regard to the admissibility of evidence, and therefore, analyzing  the case law on this issue is worth of attention.